How Fear Can Inhibit Innovation: Bottlenecks in Change Management and Strategy Development - Denisa Ligia MATEI (Communications of International Proceedings, 2022)
We live in troubled times. The social distance imposed by COVID-19, the new limitations of working from home have made people more and more lonely. Loneliness caused them anxiety, fear and blockages. If individuals ignore them, managers can't apologize. One of the elements analyzed in change management is the context in which the company operates. Michael Porter is the one who introduced the concept of the five forces that define the competitive advantage of the company. No company can grow healthily or make strategic changes if it does not know the current market players, but also the potential ones to enter, but also to understand how the demand and supply from customers evolve. Another blockage that can occur in change management is due to a lack of understanding of the macroeconomic context. It can influence through monetary policy, fiscal policy, legislative changes, economic cycles and so on. However, a major impact that will be analyzed in this article is the impact of cognitive limitations, fear that inhibits innovation and creativity. The paper examines how fear affects people's decisions based on the study of several theories. The analysis is qualitative. Change management is caused by various blockages that occur in organizations. They need to be addressed, anticipated and mitigated. Fear does not allow the individual to develop harmoniously, does not allow him to achieve his goals and does not allow him to integrate into society. A number of attributes will be discussed in this article and a number of solutions will be proposed. Managers are still a decisive factor in these situations that arise.
Keywords: Vulnerability; Fear; Blockages; Change; Decisions; Competitiveness